NZO/HlLtJ as a novel model for the studies on the role of metabolic syndrome in acute radiation toxicity. (2nd January 2020) - Ewing, Laura E.; Miousse, Isabelle R.; Pathak, Rupak; Skinner, Charles M.; Kosanke, Stanley; Boerma, Marjan; Hauer-Jensen, Martin; Koturbash, Igor
Abstract: Purpose: Growing rates of metabolic syndrome and associated obesity warrant the development of appropriate animal models for better understanding of how those conditions may affect sensitivity to IR exposure. Materials and methods: We subjected male NZO/HlLtJ mice, a strain prone to spontaneous obesity and diabetes, to 0, 5.5, 6.37, 7.4 or 8.5 Gy ( 137 Cs) of total body irradiation (TBI). Mice were monitored for 30 days, after which proximal jejunum and colon tissues were collected for further histological and molecular analysis. Results: Obese NZO/HlLtJ male mice are characterized by their lower sensitivity to IR at doses of 6.37 Gy and under, compared to other strains. Further escalation of the dose, however, results in a steep survival curve, reaching LD100/30 values at a dose of 8.5 Gy. Alterations in the expression of various tight junction-related proteins coupled with activation of inflammatory responses and cell death were the main contributors to the gastrointestinal syndrome. Conclusions: We demonstrate that metabolic syndrome with exhibited hyperglycemia but without alterations to the microvasculature is not a pre-requisite of the increased sensitivity to TBI at high doses. Our studies indicate the potential of NZO/HlLtJ mice for the studies on the role of metabolic syndrome in acute radiation toxicity.